2018
DOI: 10.1186/s13014-018-0975-4
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus-sparing radiotherapy using volumetric modulated arc therapy (VMAT) to the primary brain tumor: the result of dosimetric study and neurocognitive function assessment

Abstract: BackgroundWe hypothesized that hippocampal-sparing radiotherapy via volumetric modulated arc therapy (VMAT) could preserve the neurocognitive function (NCF) of patients with primary brain tumors treated with radiotherapy.MethodsWe reviewed data from patients with primary brain tumors who underwent hippocampal-sparing brain radiotherapy via VMAT between February 2014 and December 2015. The optimization criteria for the contralateral hippocampus was a maximum dose (Dmax) of less than 17 Gy. For NCF evaluations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…For the hippocampus, recent radiotherapy optimization studies have aimed at reducing maximum dose to 16-17 Gy and minimum dose to 9 Gy in hippocampus-sparing whole-brain radiotherapy (14,25). However, while a significant correlation was observed between mean dose to the left hippocampus and cognitive deterioration (25) as well as hippocampal volume reduction (41), no dose cut-off was defined in these studies. Hippocampus volume loss was observed to be significant one year after high-dose radiotherapy (> 40 Gy), but not after low-dose radiotherapy (< 10 Gy) by Seibert et al (42).…”
Section: Clinical Significance Of the Dosimetric Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the hippocampus, recent radiotherapy optimization studies have aimed at reducing maximum dose to 16-17 Gy and minimum dose to 9 Gy in hippocampus-sparing whole-brain radiotherapy (14,25). However, while a significant correlation was observed between mean dose to the left hippocampus and cognitive deterioration (25) as well as hippocampal volume reduction (41), no dose cut-off was defined in these studies. Hippocampus volume loss was observed to be significant one year after high-dose radiotherapy (> 40 Gy), but not after low-dose radiotherapy (< 10 Gy) by Seibert et al (42).…”
Section: Clinical Significance Of the Dosimetric Improvementsmentioning
confidence: 99%
“…Furthermore, the hippocampus has been identified as an additional critical structure of radiation-induced cognitive deficits, which has not been considered in previous studies on nTMS in radiotherapy. In addition to the observed negative impact of whole-brain radiotherapy on cognitive outcome (14,15), several studies have focussed on the hippocampus itself as one of the most critical structures for radiation injury owing to the ongoing neurogenesis in the subgranular zone of its dentate gyrus (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Higher dose to the hippocampus has particularly been associated with impaired verbal memory and higher executive functions (20,25).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that techniques allowing selective avoidance of the hippocampal neural stem-cell compartment cause a lower degree of cognitive impairment relative to WBRT [13,48]. With the development of IMRT, volumetric-modulated arc therapy (VMAT) and intensity modulated proton therapy (IMPT), hippocampal-sparing WBRT has been increasingly used as an adjuvant to surgery in the treatment of primary brain neoplasms and in management of brain metastases [49][50][51]. The results of ongoing randomized clinical trials will help to clarify the role of hippocampal-sparing WBRT in cognitive preservation [45,46,52].…”
Section: Improvement Of Techniques In Radiation Therapymentioning
confidence: 99%
“…According to the National Comprehensive Cancer Network guidelines, PCI is the standard treatment for both extensive and limited-stage SCLC, and methods of reducing neurocognitive dysfunction within the scope of PCI need to be determined. According to previous dosimetric studies, neurocognitive dysfunction occurs because the mean dose to the hippocampus exceeds approximately 19–20 Gy 21 . Besides HA-PCI, lowering the WBRT dose could be an alternative method.…”
Section: Discussionmentioning
confidence: 99%